PENGEMBANGANMEDIACONGKLAKPADAMATAPELAJARAN MATEMATIKAMATERI POKOKOPERASI HITUNGPERKALIAN DANPEMBAGIANKELASIIISDN 7 PEMENANG BARAT - Yuntawati, Yuntawati; Aziz, Lalu Abdul (Jurnal Ilmiah IKIP Mataram, 2018)
The purpose of this research is to produce conglak media on mathematics subject of multiplication counting operation and class division III SDN 7 Winner of West. This research is a development research. The subjects of the study were the third grade students of SDN 7 West Winner, amounting to 13 people. This research and development is done by using Borg and Gall development which consists of 10 (stages). However, based on the development needs that researchers will do then the stages are simplified into 5 stages are: needs analysis, design, prototype, field trials, and revisions. The results of this development research shows that the product developed in the form of congklak media can be said to be suitable for use in learning. Based on the results of validation experts note that congklak media products on learning mathematics are categorized "good" with the following criteria: from media experts categorized well with the average score of 4 while from the material experts are also in good category with the acquisition score 3.6. In addition, the results of development research obtained average data on the percentage of student responses in response to congklak media reached 92%. So that learning by using cogklak media is said to be effective, because students are very responsive to learning media congklak. While the results of student learning obtained data average score of students is 80 with the percentage of completeness reached 85%. Based on the results of this study can be concluded that the product development congklak media feasible used in school learning.